If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5t + 7 = 11t + -25 Reorder the terms: 7 + -5t = 11t + -25 Reorder the terms: 7 + -5t = -25 + 11t Solving 7 + -5t = -25 + 11t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-11t' to each side of the equation. 7 + -5t + -11t = -25 + 11t + -11t Combine like terms: -5t + -11t = -16t 7 + -16t = -25 + 11t + -11t Combine like terms: 11t + -11t = 0 7 + -16t = -25 + 0 7 + -16t = -25 Add '-7' to each side of the equation. 7 + -7 + -16t = -25 + -7 Combine like terms: 7 + -7 = 0 0 + -16t = -25 + -7 -16t = -25 + -7 Combine like terms: -25 + -7 = -32 -16t = -32 Divide each side by '-16'. t = 2 Simplifying t = 2
| 3x-5=-5-2x | | -8x+5=23 | | (16+2x)X(12+2x)=320 | | 7x(5x+10)=7x | | 4(4-4k)=-10-16 | | 16x-8=36 | | 1x+-4+2x=14 | | 10v-3-v=0 | | -2t^2+8t+1=0 | | -5t+7=11+-25 | | 4x+x+5=54 | | 8x^2y+8y=2x | | -9k+10-8k=0 | | -.250y+2=0 | | 180=(7x-3)(12x-7) | | 7-6x=-23 | | 2x-9=1-3x | | 5(x+10)=7x | | -8x+3(x-7)=-36 | | 8.5x+1.1=2.5x+2.25 | | -7-3x=4 | | 4(2x+6)=72 | | -4x-11=3x+10 | | 3(y^2-y+1)= | | -2x-5x=21 | | 4v^2+13v+5=-5 | | 12x-10=-2+12 | | -5v-8-10-8v=0 | | 5x+7+22=EF | | 16y-10=10y-5 | | (x-6)(x+5)=12 | | 18-(-f)=101 |